VIABILITY OF THE CREATION OF A UNIVERSITY INCUBATOR WITH A VIEW TO BENEFIT THE RURAL AND INDIGENOUS POPULATION OF THE STATE OF QUERÉTARO - Velázquez Hernández, Jorge Arturo; Romero Zepeda, Jorge Adán; Alonso Chombo, Rosalía; Muñoz Guevara, Epigmenio (Archives of Business Research, 2021)
The objective of this work is to analyze the feasibility of creating a university incubator (INCUERUAQ) aimed at benefiting the rural and indigenous population of the state of Querétaro. On the one hand, INCUERUAQ would represent the propitious scenario so that current students and those who are graduating, have the necessary spaces in order to face and solve problems of a technical and economic nature that may exist in their communities, always counting on the guidance of its professors and, on the other hand, the Autonomous University of Querétaro (UAQ) would establish a permanent link with rural and indigenous communities, providing them with continuous advice in areas such as legal, administrative, marketing, etc., providing for this, the necessary infrastructure that allows them to carry out their ventures successfully, facilitating, among other things, training to access the various sources of financing, when required. The methodology with which it is intended to work is participatory research, whose initiation will be marked by a diagnosis that helps to visualize how feasible this project would be, it would also allow to devise the best incubator model to implement, in such a way that they can be carried out in practice the pre-incubation, incubation and post-incubation periods. This article aims to reflect an advance of the initial stage of the link, the diagnosis.